ANALISIS PENGARUH FAKTOR INTERNAL (INTELEGENSI, MINAT, BAKAT, MOTIVASI, USIA) DAN FAKTOR EKSTERNAL (LINGKUNGAN, PENDIDIKAN, PENGALAMAN, PELATIHAN) TERHADAP PEMAHAMAN PEMBIAYAAN MUDHARABAH DAN MURABAHAH (STUDI PADA BMT DI KABUPATEN KEBUMEN) - Kusuma, Wati (Fokus Bisnis, 2013)
This study was conducted at Baitul Maal Wa Tamwil (BMT) employee who join in BMT Association of Kebumen Regency. This study is entitled âThe Effect Analysis of Internal Factors (Intelligence, Interests, Talent, Motivation, Age) and External Factor (Environment, Education, Experience, Training) toward Understanding of Mudharaba and Murabahah " (Case Study at BMTâs employee of Kebumen Regency). This study aims to determine the BMT employeeâs understanding of mudharabah and murabahah finance, and also the effect of intelligence, interests, talents, motivation, age, environment, education, experience and training toward the understanding of mudharabah and murabahah finance. The sample method used in this study is sampling purposive, i.e., BMT employee consists of Operations Manager, Marketing Manager, Finance Manager and Marketing who are in 60 respondents with a minimum term of 1 year. The analytical tool used is multiple regression analysis. Based on the study and data analysis, it can be concluded that BMT employee understands on mudharabah finance. Intelligence, talent, and training signficantly effect to mudharabah finance, whereas interests, motivation, age, environment, education and experience insignificantly effect to mudharabah finance. It can be known that BMT employee understands on murabahah. Intelligence, talent, motivation and training significantly effect to murabahah, whereas interest, age, environment, education and experience insignificantly effect on the understanding of murabahah.